Governance in developing Asia public service delivery and empowerment - Deolalikar, Anil B.; Jha, Shikha; Quising, Pilipinas F. (Edward Elgar Publishing, 2015)
Governance in Developing Asia is one of the first books of its kind to provide an overview of the role that better governance and citizen empowerment can play in improving public service delivery in developing Asia. The World Development Report 2004 set a framework for public service delivery in terms of the short and long roads to accountability of service providers to citizens. More than a decade on, this important book revisits the issue and departs from the WDR framework, highlighting its shortcomings and offering alternative solutions.